Three-Phase 75 kW Brushless Direct Current Motor for Electric Vehicles: Different Power Stage Design, Calculation of Losses, Cooling Techniques, and Comparison - Bahadir, Ali; Aydogdu, Omer; Bahadir, Elif (MDPI, 2024)
This study focuses on determining the technical specifications and parameters of an all-electric passenger vehicle, modeling it according to these parameters, selecting the appropriate electric motor as a result of the modeling, and then designing and making a new 75 kW three-phase DC-AC converter (inverter) as per to automotive standards for the brushless DC motor used for vehicle propulsion. Three different power stage designs are conducted and compared. The system losses were calculated, and three variants of cooling systems were used for cooling the power stage to reduce losses. Performances of such cooling systems were compared. Air cooling, fan-assisted air cooling, and liquid cooling structures are designed for power stage cooling, and the performances of these three systems were compared.
Keywords: brushless DC motor; electric vehicles (EV); power stage; cooling system; losses; Chemistry; Engineering; Materials Science; Physics